Experimental and numerical study on steel ring restrainers with rectangular section. (February 2021) - Sun, Jubo; Zhang, Qiang; Wang, Zhanfei; Li, Hang; Ge, Hanbin
Abstract: In this paper, steel ring restrainers (SRRs) with rectangular section are newly developed as an unseating prevention device for bridges, and results of experiments and corresponding finite element (FE) analyses of the twenty-six SRR specimens are presented. Through the monotonic tests and FE analyses, an extensive parametric study was performed to assess the effect of each parameter on the mechanical behavior of the SRRs. Not only the configuration parameters such as the sectional area and aspect ratio of the cross-section, the radius of the curved part, the length of the straight part and the diameter of the guide pulley, but also the friction coefficient between the steel ring and guide pulley and the material type of the steel ring are considered as parameters. Moreover, prediction formulas were proposed based on the parametric study. The experimental and analytical results show that while keeping the original advantages of the circular-section SRRs proposed in a previous study, the strategy of altering the cross-section shape of the steel ring from circle to rectangle is effective to compensate for its deficiencies. Derived formulas give predictions close to force-displacement curves of the SRR specimens and numerical models. Accordingly, the formulas can be expected to predict the force-displacement curves of the SRRs. Graphical abstract: Unlabelled Image Highlights: A strategy to compensate for defects of steel ring restrainers (SRRs) with a circular section was proposed. Monotonic tests of twenty-six specimens were conducted to investigate the behavior of SRRs with a rectangular section. FE models were developed to further assess the effect of each parameter on the mechanical behavior of SRRs. behavior of the SRRs. Predicted formulas with six parameters as variables were derived to evaluate the force-displacement curves of SRRs.